Intercropping Land Kale on Hypopodium Leftover Oil Palm Fronds Pruning - Ramadhan, Ardian; Nasution, Dwiky Ardiansyah (International Journal of Oil Palm, 2024)
The horticultural consumption of land kale in Indonesia is still quite high due to its complete nutritional content. However, limited cultivation land is an obstacle to the production of land kale. On the other hand, Indonesia has a very large area of oil palm plantations because it is a superior commodity as a foreign exchange earner. But it is unfortunate that the output obtained is only oil palm fresh fruit bunches (FFB). Therefore, it is necessary to create an integrated agricultural model such as intercropping so that the output obtained is more and profitable economically and environmentally sustainable. Intercropping is a method of agricultural cultivation by planting two or more commodities in the same area to maximise land use and maximise productivity. Intercropping in oil palm is not carried out in producing crops (TM) due to constraints on cultivation land area. However, by using a new agricultural cultivation method, namely cultivation on the hypopodium of the remaining leaf pruning, oil palm producing plants (TM) can still be intercropped. Hypopodium is the tip or base of the leaf that connects to the plant stem. The hypopodium area that is already wide enough in producing plants (TM) can be used as a place for kale plant growth. In addition, the content of organic matter in the hypopodium can be used as a source of nutrients and as an organic substrate. This type of primary research with qualitative methods shows the results that the intercropping method of kale with oil palm on the hypopodium of the remaining pruning of oil palm leaves can be done so that the output out of the farm is more.